Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1034/j.1600-0609.2003.00093.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary treatment with autologous stem cell transplantation in mantle cell lymphoma: outcome related to remission pretransplant

Abstract: In MCL, an important strategy to improve the outcome will be to intensify the induction chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 24 publications
4
69
0
2
Order By: Relevance
“…Chemotherapy using cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP) does not seem to result in a relevant reduction of tumor load in PB, BM, or PB stem cell products, even among patients who achieve a clinical remission, as reported in the Nordic MCL1 study 5 and a single-center series of homogeneously treated patients (Table 2). 16 Immunochemotherapy with rituximab plus CHOP (R-CHOP) in the MCL Younger and MCL Elderly trials showed (for the first time) relevant rates of molecular remission (MRD negativity) of 40%, with 21% of patients MRD negative already at midterm induction.…”
Section: Mrd During and After Induction Treatmentmentioning
confidence: 96%
See 2 more Smart Citations
“…Chemotherapy using cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP) does not seem to result in a relevant reduction of tumor load in PB, BM, or PB stem cell products, even among patients who achieve a clinical remission, as reported in the Nordic MCL1 study 5 and a single-center series of homogeneously treated patients (Table 2). 16 Immunochemotherapy with rituximab plus CHOP (R-CHOP) in the MCL Younger and MCL Elderly trials showed (for the first time) relevant rates of molecular remission (MRD negativity) of 40%, with 21% of patients MRD negative already at midterm induction.…”
Section: Mrd During and After Induction Treatmentmentioning
confidence: 96%
“…Four studies consistently reported that the presence of or the relative content of tumor cells in the stem cell product did not affect further clinical outcome. 5,16,29,31 This could indicate that tumor cells contaminating the reinfused stem cells might not be able to cause or promote clinical progression, and that cytoreduction in the involved tissues by induction and consolidation treatment has the strongest impact on tumor control.…”
Section: Prognostic Value Of Mrd Before High-dose Consolidationmentioning
confidence: 99%
See 1 more Smart Citation
“…6,[9][10][11] The superior outcome of patients transplanted in CR1 has been a consistent finding in most reported series, and argues for the application of high-dose therapy with autologous HPCT as part of the primary treatment. 5,[12][13][14][15][16] Nevertheless, it remains unclear whether autologous HPCT is actually curative, and the optimal timing of transplantation remains a point of debate.…”
Section: Introductionmentioning
confidence: 83%
“…9,12 In our patient population, 16 patients (76%) were in CR1 at the time of transplant and five patients (24%) were in PR1. There was one biopsy-proven late relapse 9 years post transplant; the remaining three relapses occurred 1.8, 2 and 2.9 years after transplant.…”
Section: Discussionmentioning
confidence: 99%